Produksi dan potensi padang penggembalaan alam Desa Bangka Kantar Kecamatan Borong Kabupaten Manggarai Timur - Herman Yosep Nasar; Herayanti Panca Nastiti; Stefanus Tani Temu (Jurnal Peternakan Lahan Kering, 2019)
The study was carried out in Desa Bangka Kantar, Kecamatan Borong, Kabupaten Manggarai Timur, for one month, divided into 2 periods: pre-survey and data collection. The study aimed at forage productivity, botanical composition and carry capacity of wild pasture in Desa Bangka Kantar, Kecamatan Borong, Kabupaten Manggarai Timur. Survey method by on the field observation technique to collect primer data was applied. Collected data were tabulated to find out the average of forage productivity, botanical composition, and carry capacity of the pasture. The results found were: forage productivity: 2274.79 Kg/Ha fresh or 756.14 Kg/Ha DM weight which can be shepherd for 0.44AU/Ha; botanical composition consisted of 67.26% grass and 19.73% legume. The conclusion is that forage productivity and carry capacity of wild pasture in Desa Bangka Kantar are low which is composed mainly by grass.